2020
DOI: 10.1007/978-3-030-54820-9
|View full text |Cite
|
Sign up to set email alerts
|

The Axiological Status of Theism and Other Worldviews

Abstract: Palgrave Frontiers in Philosophy of Religion is a long overdue series which will provide a unique platform for the advancement of research in this area. Each book in the series aims to progress a debate in the philosophy of religion by (i) offering a novel argument to establish a strikingly original thesis, or (ii) approaching an ongoing dispute from a radically new point of view. Each title in the series contributes to this aim by utilising recent developments in empirical sciences or cutting-edge research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…134 Kahane includes loss of privacy in this cluster of anti-theistic considerations. Following Lougheed (2020b), I have treated it separately because there is a larger literature that concerns it. 135 Lougheed (2020b, chapter 4) notes that many theists believe that an important purpose God assigns to persons is to pursue a relationship with God, and he endorses a principle articulated by Metz (2013b: 103) to the effect that it is disrespectful to create any person for any purpose other than to pursue its own purposes.…”
Section: Loss Of Dignitymentioning
confidence: 99%
“…134 Kahane includes loss of privacy in this cluster of anti-theistic considerations. Following Lougheed (2020b), I have treated it separately because there is a larger literature that concerns it. 135 Lougheed (2020b, chapter 4) notes that many theists believe that an important purpose God assigns to persons is to pursue a relationship with God, and he endorses a principle articulated by Metz (2013b: 103) to the effect that it is disrespectful to create any person for any purpose other than to pursue its own purposes.…”
Section: Loss Of Dignitymentioning
confidence: 99%
“…I explained that I hoped ‘to show the method that can be applied to each good in order to discover how such goods can obtain without God. On the assumption the goods I examine are representative of the theistic goods in general, then this method can be applied other theistic goods that I don't examine’ (Lougheed (2020), 180). I then argued that theistic advantages such as cosmic justice, a good afterlife, divine intervention, no gratuitous evil, relationship with a maximal being, and salvation can all obtain in atheist worlds ( ibid ., 181–186).…”
Section: Kahane's Argumentmentioning
confidence: 99%
“…Though, depending on the relevant set of goods, and on how loosely we understand ‘naturalism’, it can hardly be ruled out in advance that we could enjoy many of these goods in a conceivable naturalist universe. (Kahane (2018), 102–103)Now, while Kahane is right that this cannot be ruled out in advance, I have suggested that it's quite doubtful the best atheist worlds can be naturalistic given the nature of some of the advantages and disadvantages in question (Lougheed (2020), 180). While in what follows I won't explicitly defend the claim that the very best worlds are supernatural, I will flag points in the discussion below that support this claim.…”
Section: Kahane's Argumentmentioning
confidence: 99%
See 2 more Smart Citations